1999
DOI: 10.1002/(sici)1521-3773(19990115)38:1/2<153::aid-anie153>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Metal-Organic Large-Pore Zeotype

Abstract: A significant step towards the development of a new family of metal‐organic zeolite analogues has been achieved by binding zinc ions to the anion of 4,6‐di(1‐imidazolyl)‐1,3,5‐triazine‐2‐one to produce a novel uncharged large‐pore zeotype capable of incorporating a range of guest molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…In the last few years, much effort has been devoted to the use of transition metal ions with exo-bidentate ligands, such as polypyridyl or pyrazines and 1,4-benzenedicarboxylate, to generate polymeric metal±organic coordination polymers with two-or three-dimensional networks. Very recently, Goodgame et al (1999) reported a new type of metal±organic large-pore zeotype, i.e. [Zn(dimto) 2 ] n ÁnDMF [dimto = 2,4,6-tri(1-imidazolyl)-1,3,5-triazin-2-one], which was generated from zinc bromide and 2,4,6-tri(1-imidazolyl)-1,3,5-triazine (timt).…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, much effort has been devoted to the use of transition metal ions with exo-bidentate ligands, such as polypyridyl or pyrazines and 1,4-benzenedicarboxylate, to generate polymeric metal±organic coordination polymers with two-or three-dimensional networks. Very recently, Goodgame et al (1999) reported a new type of metal±organic large-pore zeotype, i.e. [Zn(dimto) 2 ] n ÁnDMF [dimto = 2,4,6-tri(1-imidazolyl)-1,3,5-triazin-2-one], which was generated from zinc bromide and 2,4,6-tri(1-imidazolyl)-1,3,5-triazine (timt).…”
Section: Commentmentioning
confidence: 99%
“…Very recently, Goodgame and Williams reported a new type of metal-organic largepore zeotype, i.e. [Zn(dimto) 2 ] n .nDMF [dimto = 2,4,6-tri(1-imidazolyl)-1,3,5-triazin-2-one], which was generated from zinc bromide and 2,4,6-tri(1-imidazolyl)-1,3,5-triazine (timt) (Goodgame et al, 1999). Li et al (1999) reported a porous polymer, [{Zn 4 O(bdc) 3 }(dmf) 8 (C 6 H 5 Cl)] n (bdc = 1,4-benzenedicarboxylate), which could absorb and disabsorb nitrogen gas.…”
Section: Crystal Datamentioning
confidence: 99%
“…16,17 Two-or three-connecting ligands have been proved to be one of the most important ligands in construction of novel frameworks. [18][19][20][21][22][23] However most of these reported complexes are formed by assembly of the rigid ligands with metal ions, the reported flexible tripodal ligands with aromatic core in this field are relatively rare. [24][25][26][27] In the case of flexible ligands, the possible coordination modes are much more abundant than those of the rigid one due to the flexibility and low symmetry of the ligands since the flexible ligands can adopt different conformations according to the geometric needs of different metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the behavior of metal chelation, which has been one of the most active areas in the ®elds of chemistry and material sciences, shows promising prospects in applications (Schnebeck et al, 1999;Abrahams et al, 1998;Goodgame et al, 1999;Albrecht, 1985). Chelidamic acid (4-hydroxypyridine-2,6-dicarboxylic acid), an polydentate ligand, is of considerable interest in coordination chemistry.…”
Section: Commentmentioning
confidence: 99%